2019
DOI: 10.1103/physrevlett.123.102501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Rigid Triaxial Deformation in Ge76 from a Model-Independent Analysis

Abstract: An extensive, model-independent analysis of the nature of triaxial deformation in 76 Ge, a candidate for neutrinoless double-beta (0νββ) decay, was carried out following multi-step Coulomb excitation. Shape parameters deduced on the basis of a rotational-invariant sum-rule analysis provided considerable insight into the underlying collectivity of the ground-state and γ bands. Both sequences were determined to be characterized by the same β and γ deformation parameter values. In addition, compelling evidence fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 43 publications
1
14
2
Order By: Relevance
“…The Q 2 values of the ground states in 70−76 Ge have similar values of about 0.2 e 2 b 2 , while those of the 0 + 2 states evolve considerably, from being consistent with zero in 74,76 Ge [199,200], almost identical with that of the ground state in 72 Ge [196,197]), to a value of 0.64(26) e 2 b 2 in 70 Ge [198]). The recent detailed Coulomb-excitation studies of 72 Ge [196] and 76 Ge [201] have also confirmed a rotational character of the ground-state bands in these nuclei, with the Q 2 values being remarkably constant up to spin 8. The only significant deviation from this pattern is a slight reduction observed for the 0 + 1 state in 72 Ge, which may be attributed to the strong mixing with a less deformed configuration.…”
Section: Neutron-deficient Nuclei With N ≈ Zmentioning
confidence: 78%
“…The Q 2 values of the ground states in 70−76 Ge have similar values of about 0.2 e 2 b 2 , while those of the 0 + 2 states evolve considerably, from being consistent with zero in 74,76 Ge [199,200], almost identical with that of the ground state in 72 Ge [196,197]), to a value of 0.64(26) e 2 b 2 in 70 Ge [198]). The recent detailed Coulomb-excitation studies of 72 Ge [196] and 76 Ge [201] have also confirmed a rotational character of the ground-state bands in these nuclei, with the Q 2 values being remarkably constant up to spin 8. The only significant deviation from this pattern is a slight reduction observed for the 0 + 1 state in 72 Ge, which may be attributed to the strong mixing with a less deformed configuration.…”
Section: Neutron-deficient Nuclei With N ≈ Zmentioning
confidence: 78%
“…Transitions were detected with the GRETINA tracking array [42] in coincidence with the two reaction partners measured by the CHICO2 compact heavy ion counter [43], as described in Ref. [44]. The resulting yields were analyzed with the semiclassical Coulomb excitation code, GOSIA [45], which provided electromagnetic matrix elements for transitions from 13 states [46].…”
mentioning
confidence: 99%
“…On the other hand, multiple lowenergy Coulomb-excitation studies of stable Ge and Zn isotopes [14,25,28] demonstrated the importance of the triaxial degree of freedom in their structure, which was also evoked for the neighbouring 76,78 Se nuclei [29,30]. Particularly relevant is the study of 76 Ge [31], which yielded (β 2 , γ) parameters for the 0 + 1 , 2 + 1 and 2 + 2 states and their dispersions, which are consistent with rigid triaxial deformation. This is particularly important considering that 76 Ge is a candidate for searches of neutrinoless double-β decay, and the nuclear shape is predicted to play a significant role in this process [32,33].…”
Section: Shape Coexistence Triaxiality and The N = 50 Shell Closure In Germanium And Zinc Isotopesmentioning
confidence: 85%